Regular show. 25 years later - Hastings, Chris, 1983-; Quintel, J. G. (James Garland), 1982- (Kaboom!, a division of Boom Entertainment, Inc., 2019)
"Twenty-five years after the epic battle between Pops and Anti-Pops, Mordecai, Rigby, and the rest of their friends return to the park for a reunion! Their crazy youth is nothing but a memory... or so Mordecai and Rigby think. It's not long before these two friends stumble across a secret fairy world, find themselves young again, and have their children stolen by Viceroy Alberich, the Fairy King. Now 25 years younger, Mordecai and Rigby must work together to reform Alberich's miscreant children if they want their own returned to them."--Provided by publisher.